Simultaneous Cooperation and Competition in the Evolution of Musical Behavior: Sex-Related Modulations of the Singer's Formant in Human Chorusing - Keller, Peter E.; König, Rasmus; Novembre, Giacomo (Frontiers in Psychology, 2017)
Human interaction through music is a vital part of social life across cultures. Influential accounts of the evolutionary origins of music favor cooperative functions related to social cohesion or competitive functions linked to sexual selection. However, work on non-human “chorusing” displays, as produced by congregations of male insects and frogs to attract female mates, suggests that cooperative and competitive functions may coexist. In such chorusing, rhythmic coordination between signalers, which maximizes the salience of the collective broadcast, can arise through competitive mechanisms by which individual males jam rival signals. Here we show that mixtures of cooperative and competitive behavior also occur in human music. Acoustic analyses of the renowned St. Thomas Choir revealed that, in the presence of female listeners, boys with the deepest voices enhance vocal brilliance and carrying power by boosting high spectral energy. This vocal enhancement may reflect sexually mature males competing for female attention in a covert manner that does not undermine collaborative musical goals. The evolutionary benefits of music may thus lie in its aptness as a medium for balancing sexually motivated behavior and group cohesion.